Thermal springs and active fault network of the central Colca River basin, Western Cordillera, Peru - Tyc, Andrzej (2022)
Thermal waters and vapor discharges (hot springs, geysers, solfataras, and fumaroles) are common phenomena in volcanic regions at active plate boundaries, and the Central Andes are no exception. The Colca River basin in S Peru is a highly diversified and complex thermal region with unresolved questions on the origin of thermal fluids, reservoir temperature, and connections with tectonic and/or volcanic activity. To answer these, we used hydrogeochemical analysis of 35 water samples from springs and geysers, together with isotopic (δ18O and δD) analysis, chemical and mineral studies of precipitates collected in the field around these outflows, and field observations. We aimed (1) to recognize the geochemistry of thermal waters and precipitates in the central part of the Colca River basin, (2) to identify fluid sources and their origin, (3) to estimate the temperature of a potential geothermal reservoir, and (4) to discuss the regional active tectonic and volcanic framework of this geothermal region and mutual relationships. Our results corroborate a heterogeneous and complex geothermal system in the central part of the Colca River basin, with contrasting hydrogeochemical and physical properties, variable isotope composition, different reservoir temperatures, and associated precipitates around thermal springs. Processes controlling water chemistry are closely related to the Ampato-Sabancaya magmatic chamber's activity and tectonic structures that allow complex interactions of meteoric waters with magmatic fluids and gases. With a considerable gradient of pressure owing to local relief and deep incision in the Colca Canyon, these processes led to the differentiation of the thermal waters into three main groups. (1) Chloride-rich, mainly sodium chloride, thermal waters are of meteoric origin but mature within the geothermal reservoir possibly fed by magma degassing. These waters' chemical and isotopic composition results from water-rock interaction and mixing with magmatic waters within the reservoir. These waters discharge at the bottom of the Colca Canyon and Valley, presenting a broad hydrogeochemical spectrum and highly variable mineral phases precipitating at the outflows. The reservoir temperature estimated for these waters ranges from 180 to 200 °C. The group of hottest springs and geysers at the bottom of the Colca Canyon waters are fully equilibrated, with the reservoir temperature ~ 240 °C. (2) Sulfate-rich waters are shallow meteoric waters heated by ascending gases that form an independent group referring to the local water circulation, often controlled by tectonic barriers. (3) Bicarbonate-rich waters are the intermediate meteoric waters, divided into two hydrochemical groups: waters partially equilibrated with reservoir rocks and more similar to chloride-rich waters or additionally enriched with SO4 and more similar to sulfate-rich waters. Studied thermal springs show a clear spatial correlation with active and seismogenic crustal W- to NW-tracing normal and strike-slip faults. These act as barriers to infiltrating meteoric waters, provide pathways to hydrothermal solutions and gases assisting in meteoric water heating, and yield passages for pressured by lithostatic load and heated waters to ascend to the surface.